Menos direitos, mais desigualdades - uma análise da questão previdenciária à luz das assimetrias regionais no Brasil - Silva, Caio Jisman dos Santos (2020)
The topicality of the topic of social security is proven by observing the debates in the media and at the congress, where it is commonly pointed out as an unnecessary expense for the government. On a regional scale, this discussion becomes even more pertinent, considering that social security benefits in the poorest regions are an important (or perhaps the main) source of household income. In this sense, the main objective of this dissertation is to analyze the relationship between regional inequalities and Brazilian social security, based on the study of social security reforms carried out since the last years of the 20th century. Therefore, the search for answers to the following question was used as a starting point: what are the characteristics of the relationship between regional inequalities and the Brazilian social security system? In the scope of economic theory, the framework of regional development and uneven and combined development was used. Through the structuralist method and through descriptive statistics and bibliographic research, it was possible to analyze the Brazilian social protection system as a structure capable of producing effects on regional inequalities. The results of this research showed that there are multiple regional socioeconomic inequalities and different demographic characteristics that need to be considered before any reform of universal social policies, such as social security. The paths used by the State to correct structural problems in social security, in addition to resolving the social rights guaranteed by the Federal Constitution of 1988, have been moving in the opposite direction to the idea of solidarity and universality of the system. Furthermore, social security reforms, based on a false diagnosis promoted by an analysis based on neoliberal parameters, have contributed to the maintenance and even worsening of regional inequalities.